Glass substrate, chemically strengthened glass, cover glass and electronic equipment

By adding rare earth oxides to the glass substrate, visible and near-infrared light are converted into ultraviolet light, the sterilization efficiency of TiO2 is improved, the problem of low sterilization efficiency of existing glass substrates is solved, and the mechanical properties of the glass are enhanced.

CN119161099APending Publication Date: 2024-12-20LILING KIBING ELECTRONIC GLASS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411177989.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing glass substrates have low sterilization efficiency under sunlight, especially on touch display screens of electronic devices, where bacterial growth poses potential hazards.

Method used

By adding rare earth oxides into the glass substrate, the visible and near-infrared light are converted into ultraviolet light by using electron transitions of rare earth elements, so that TiO2 can effectively perform photocatalytic sterilization and improve sterilization efficiency.

Benefits of technology

It significantly improves the sterilization efficiency of TiO2 under sunlight, enhances the antibacterial ability of the glass substrate, and improves the thermal stability, mechanical strength and impact resistance of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005011311410000081
    Figure BDA0005011311410000081
Patent Text Reader

Abstract

The invention relates to the technical field of glass preparation, and provides a glass substrate which comprises the following components in percentage by mass based on 100% of the total mass: 50%-70% of SiO2, 10%-20% of SiO2, 10%-20% of SiO2, 10%-20% of SiO2, 10%-20% of SiO2 and 10%-20% of SiO2. 4% to 20% of Al2O3; r2O: 12.5% to 20%; 0%-9% of MgO; 2%-5% of TiO2; in the formula, R2O is at least one of K2O, Na2O or Li2O, R2O is at least one of K2O, Na2O or Li2O, and R2O is at least one of K2O, Er2O3, Ho2O3 and Tm2O3. By doping the rare earth oxide and utilizing electron transition of rare earth elements, visible light and near-infrared light are converted into ultraviolet light through up-conversion, so that TiO2 in the glass can absorb the ultraviolet light and carry out photocatalysis, a sterilization effect is achieved, and the sterilization efficiency of TiO2 under sunlight irradiation is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of glass, and in particular relates to a glass substrate, chemically strengthened glass, cover glass and electronic equipment. Background Art

[0002] Glass materials can be found everywhere in our daily lives, from small touch screens such as mobile phone screens and computer screens to large ones such as medical monitoring equipment, automotive glass, daily glass, and building exterior glass. When people use these glass products in daily life, they will produce sweat, dust, etc., which provide favorable conditions for the growth of bacteria. In particular, the touch screens of some electronic devices need to frequently contact with human skin, which is very easy to breed bacteria and poses certain potential hazards to human health. It is necessary to inhibit the growth and reproduction of harmful bacteria.

[0003] At present, the commonly used antibacterial method is to add the antibacterial agent TiO2 to the glass, mainly using ultraviolet light for sterilization. However, ultraviolet light only accounts for about 7% of sunlight, of which about 50% is visible light and about 43% is infrared light. The sterilization efficiency under sunlight is relatively low. Summary of the invention

[0004] The purpose of the present application is to provide a glass substrate, chemically strengthened glass, cover glass and electronic equipment, aiming to solve the technical problem of low sterilization efficiency of existing glass substrates.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] In a first aspect, the present application provides a glass substrate. Taking the total mass of the glass substrate as 100%, the glass substrate includes the following components in mass percentage:

[0007] SiO2: 50%~70%; Al2O3: 4%~20%; R2O: 12.5~20%; MgO: 0%~9%; ZrO2: 0.2%~0.5%; TiO2: 2%~5%; Tb2O3+Er2O3+Ho2O3+Tm2O3: 0.05%-0.2%, wherein R2O is at least one of K2O, Na2O or Li2O.

[0008] Optionally, the glass substrate further comprises the following components in percentage by mass:

[0009] Tb2O3: 0% ~ 0.2%; Er2O3: 0.0% ~ 0.1%; Ho2O3: 0% ~ 0.2%; Tm2O3: 0% ~ 0.2%.

[0010] Optionally, the glass substrate further comprises the following components in mass percentage: Ce2O3: 0% to 0.02%; Yb2O3: 0% to 0.5%;

[0011] Define X1 = ([Yb2O3] + [Ce2O3]) / ([Tb2O3] + [Er2O3] + [Ho2O3] + [Tm2O3]), X1 is 1 to 3, wherein [Yb2O3] is the mass percentage of Yb2O3, [Ce2O3] is the mass percentage of Ce2O3,

[0012] [Tb2O3] is the mass percentage of Tb2O3, [Er2O3] is the mass percentage of Er2O3, [Ho2O3] is the mass percentage of Ho2O3, and [Tm2O3] is the mass percentage of Tm2O3.

[0013] Optionally, the glass substrate further comprises the following components in percentage by mass: CaF2: 0-2%; Ge2O3: 0%-2%; CaF2+Ge2O3: 0.05%-3%.

[0014] Optionally, X2 is 0.01 to 0.06, wherein X2 = ([CaF2] + [Ge2O3]) / [SiO2], [CaF2] is the mass percentage of CaF2, [Ge2O3] is the mass percentage of Ge2O3, and [SiO2] is the mass percentage of SiO2.

[0015] Optionally, R2O is K2O and Na2O, and the glass substrate further comprises the following components in percentage by mass: Na2O: 10% to 15%; K2O: 2.5% to 5%.

[0016] The glass substrate provided in the first aspect of the present application, by doping rare earth oxides, utilizes the electronic transition of rare earth elements to convert visible light and near-infrared light into ultraviolet light through up-conversion, so that TiO2 in the glass can absorb and perform photocatalysis, thereby playing a bactericidal role and improving the bactericidal efficiency of TiO2 under sunlight.

[0017] In a second aspect, a chemically strengthened glass is provided. The chemically strengthened glass is obtained by chemically strengthening the above-mentioned glass substrate.

[0018] In a third aspect, a cover glass is provided, wherein the cover glass comprises the glass substrate or chemically strengthened glass as described above.

[0019] In a fourth aspect, an electronic device is provided, comprising the glass substrate, chemically strengthened glass or cover glass as described above. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0021] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0022] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0023] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0024] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0025] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0026] In a first aspect of an embodiment of the present application, a glass substrate is provided. Taking the total mass of the glass substrate as 100%, the glass substrate includes the following components in mass percentage: SiO2: 50% to 70%; Al2O3: 4% to 20%; R2O: 12.5 to 20%; MgO: 0% to 9%; ZrO2: 0.2% to 0.5%; TiO2: 2% to 5%; Tb2O3+Er2O3+Ho2O3+Tm2O3: 0.05%-0.2%, wherein R2O is at least one of K2O, Na2O or Li2O.

[0027] SiO2 is a glass network former. It can reduce the thermal expansion coefficient of glass and improve the thermal stability, chemical stability, hardness and mechanical strength of glass. Too high SiO2 makes it difficult to melt the glass, and the glass's meltability is reduced and crystallization is easy; on the other hand, when it is too low, the glass loses transparency or the weather resistance is reduced; the preferred SiO2 mass percentage content is 50% to 70%.

[0028] Al2O3 in glass can improve the chemical stability, thermal stability, mechanical strength and hardness of glass. In addition, since the space gap of aluminum oxide tetrahedron is larger than the space gap of silicon oxide tetrahedron, Al2O3 enables glass to obtain a larger compressive stress layer and higher strengthening efficiency; when the content of Al2O3 is too high, the viscosity and devitrification temperature of the glass increase, and the meltability decreases; the preferred Al2O3 mass percentage content is 4% to 20%.

[0029] As an antibacterial agent, TiO2 can perform photocatalysis under ultraviolet light irradiation, thereby degrading organic matter, thereby playing a bactericidal role. In addition to the bactericidal effect, it can also improve the elastic modulus, bending strength, strain point and other properties of the glass. During the chemical strengthening process, the synergistic effect of TiO2 and CaO can improve stress relaxation, help to enhance compressive stress, improve the impact resistance of glass, and the glass strengthening effect is better. However, when the TiO2 content is high, the glass is easy to color and increase the crystallization tendency of the glass. Therefore, the TiO2 content of the present invention ranges from 1% to 5%, and can specifically be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.

[0030] Tb2O3, Er2O3, Tm2O3 and Ho2O3 are all used as up-conversion activators, which can convert visible light and infrared light into ultraviolet light that can be used by TiO2. The doping amount of these elements cannot be too high, otherwise annihilation will occur, which will lead to low up-conversion efficiency. If the doping amount is too low, the up-conversion efficiency will also be relatively low. Therefore, the total amount of Tb2O3+Er2O3+Ho2O3+Tm2O3 ranges from 0.05% to 0.2%, and can be specifically 0.05%, 0.1%, 0.15% or 0.2%.

[0031] R2O is an alkali metal oxide, including at least one of sodium oxide, potassium oxide, and lithium oxide. Alkali metal oxides, as network exosomes, provide free oxygen and flux, reduce the melting temperature, and improve the strength and chemical resistance of the glass substrate. They are ion exchange components in aluminosilicate glass. When there are too many alkali metal oxides, the glass is prone to devitrification. In addition, if the thermal expansion coefficient is increased too much, the thermal shock resistance is reduced, and it is difficult to match the thermal expansion coefficient of the surrounding materials. In addition, if the strain point is reduced too much, it is difficult to increase the compressive stress after chemical strengthening. When it is too little, the ion exchange performance or the solubility of the glass is reduced. Therefore, the total amount of R2O ranges from 12.5 to 20wt%, and preferably, the total amount of R2O ranges from 12.5 to 15wt%.

[0032] In a preferred embodiment, R2O includes only Na2O and K2O. Na2O and K2O act as network exosomes to provide free oxygen and flux, reduce the melting temperature, and improve the strength and chemical resistance of the glass substrate; K2O can replace part of Na2O, and due to the mixed alkali effect, it can improve the material properties of the glass liquid and the chemical resistance of the glass substrate while fluxing.

[0033] Specifically, Na2O is a network exosome and an ion exchange component, and is a component that reduces high temperature viscosity and improves solubility and formability. However, Na2O increases the thermal expansion coefficient of glass and reduces the chemical stability and mechanical strength of glass. In the present invention, Na2O should not be excessive, and the added mass percentage content is 10% to 15%.

[0034] K2O, as a network exosome, is beneficial for reducing high temperature viscosity, improving solubility and formability, and is also a component for increasing Vickers hardness and inhibiting devitrification. However, when the content of K2O is too high, the desired surface compressive stress cannot be obtained after chemical strengthening. The mass percentage content of K2O in the present invention is 2.5% to 5%.

[0035] MgO is an external oxide of the glass network structure. MgO can reduce the melting point of glass, improve the uniformity of glass liquid, improve the melting property of glass, increase the hydrolysis resistance and improve the durability. However, the addition of MgO tends to reduce the ion exchange performance of the product and has an adverse effect on the compressive stress depth of the product. The mass percentage content of MgO in the present invention is in the range of 0 to 9%.

[0036] ZrO2 is a common nucleating agent and can participate in the network structure of glass in the form of [ZrO4] tetrahedron and [ZrO6] octahedron, thereby improving the strain point, mechanical strength, stability and alkali resistance of glass. ZrO2 promotes the movement of sodium ions in glass and increases the surface compressive stress after chemical strengthening. However, if the ZrO2 content is too high, it will cause problems such as crystallization, difficulty in melting and excessively high forming temperature. The mass percentage of ZrO2 ranges from 0.2% to 0.5%.

[0037] The substrate glass provided by the present invention, by doping with rare earth oxides, utilizes the electronic transition of rare earth elements, and converts visible light and near-infrared light into ultraviolet light through up-conversion, so that TiO2 in the glass can absorb and perform photocatalysis, thereby playing a bactericidal role and improving the bactericidal efficiency of TiO2 under sunlight. At the same time, silicon dioxide is the network former, i.e., the skeleton, of the glass substrate. If the content is too low, the structure of the prepared glass substrate will be loose, the strength will be low, and the chemical corrosion resistance will be poor; if the content is too high, the melting temperature of the overall component will be high, which is not conducive to the mass production of the glass substrate. Aluminum oxide is an intermediate oxide. Aluminum has two coordination states in the glass substrate, i.e., tetrahedron and octahedron. When increasing the aluminum content, the present invention optimizes the combination of other components to make Al 3+ In tetrahedron, it forms a unified network with silicon-oxygen tetrahedron, which can improve the strength, toughness and chemical corrosion resistance of the glass substrate; alkali metal oxides, as the outer body of the network, provide free oxygen and have a fluxing effect, which reduces the overall melting temperature of each component and can improve the chemical resistance of the glass substrate. Therefore, titanium dioxide and rare earth elements are combined with the materials of silicon dioxide, aluminum oxide and alkali metal oxide in the above ratio, so that the glass substrate of the present application can not only improve the sterilization efficiency, but also improve the strength and toughness of the glass substrate.

[0038] Further, in some embodiments, the glass substrate further includes the following components in mass percentage: CaF2: 0-2%; Ge2O3: 0%-2%; CaF2+Ge2O3: 0.05%-3%. Ge2O3 can reduce the phonon energy of the glass, which is beneficial to reduce the probability of non-radiative transition, thereby improving the up-conversion luminescence efficiency, preferably 0-2%. CaF2 can reduce the phonon energy of the glass, which is beneficial to reduce the probability of non-radiative transition, thereby improving the up-conversion luminescence efficiency. Fluorides are evenly distributed in the oxide glass network structure, wherein the fluorides depend on the fluoride components introduced into the fluoride-oxygen glass components. Fluors mainly include CaF2, BaF2, SrF2, YF3 and LaF3, etc., and the doped rare earth ions will be preferentially enriched in the fluorides, which makes the rare earth ions in an environment with very low phonon energy, and their phonon energy can reach a minimum of 230cm -1 However, F will destroy the glass network structure and reduce the strength of the glass network structure, and the introduced Ca will be unfavorable for the subsequent chemical strengthening of the glass and will reduce the surface stress of the strengthened glass. However, the synergistic effect of Ti and Ca in the chemical strengthening process can improve stress relaxation, help enhance compressive stress, improve the impact resistance of the glass, and achieve better glass strengthening effect. Therefore, the present application preferably selects CaF2 at 0-2%, and further, CaF2+Ge2O3 is preferably 0.05%-3%, and further, (CaF2+Ge2O3) / SiO2 is preferably 0.01-0.06.

[0039] Further, in some embodiments, the glass substrate further comprises the following components in mass percentage: Ce2O3: 0% to 0.02%; Yb2O3: 0% to 0.5%;

[0040] Define X1 = ([Yb2O3] + [Ce2O3]) / ([Tb2O3] + [Er2O3] + [Ho2O3] + [Tm2O3]), X1 is 1 to 3, wherein [Yb2O3] is the mass percentage of Yb2O3, [Ce2O3] is the mass percentage of Ce2O3,

[0041] [Tb2O3] is the mass percentage of Tb2O3, [Er2O3] is the mass percentage of Er2O3, [Ho2O3] is the mass percentage of Ho2O3, and [Tm2O3] is the mass percentage of Tm2O3.

[0042] Yb2O3 and Ce2O3 are used as sensitizers. Yb2O3 has a relatively large absorption cross section at 980nm infrared light, which can enable the antibacterial glass to utilize near-infrared light. The preferred range of Yb2O3 is 0-0.5%, and Ce2O3: 0-0.02%. The ratio of X1 is further preferably 1-3, specifically 1, 1.5, 2, 2.5 or 3.

[0043] The following describes the invention in conjunction with specific embodiments.

[0044] Example 1

[0045] An embodiment of the present invention provides a glass substrate and a method for preparing the same.

[0046] A glass substrate comprises the following components, measured by the mass percentage of oxides: SiO2: 60%; Al2O3: 16%; Na2O: 14%; K2O: 3%; MgO: 3%; ZrO2: 0.3%; TiO2: 2%; CaF2: 1.5%; Ge2O3: 0.5%; Yb2O3: 0.1%; Er2O3: 0.05%; Tm2O3: 0.05%.

[0047] A method for preparing a glass substrate comprises the following steps:

[0048] S1: Weigh each component according to the formula;

[0049] S2: After mixing the components, the temperature is increased from room temperature to 1400°C at a heating rate of 10°C / min, and the temperature is kept for 150 minutes. Then, the temperature is increased from 1400°C to 1650°C at a heating rate of 6°C / min and the temperature is kept for 360 minutes to clarify and homogenize the mixture to obtain glass liquid;

[0050] S3: pouring the glass liquid into a mold for molding, cooling until the glass solidifies, and transferring it to a muffle furnace for heat preservation annealing to obtain glass;

[0051] S4: Cut, grind and polish the glass to obtain a glass substrate with a thickness of 0.7 mm.

[0052] Performance Testing

[0053] The glass substrate obtained in Example 1 was tested for the degradation rate of methyl orange dye (MO). The degradation rate test method of methyl orange dye (MO) was as follows: the prepared glass sample was placed in a methyl orange (MO) solution of a certain volume and a certain concentration. Before the photoreaction, the sample was stirred in the dark for 30 minutes to ensure that the adsorption-desorption of the dye molecules by the sample reached equilibrium and to avoid the influence of the adsorption on the catalytic efficiency during the photocatalytic process. The sunlight illumination reaction was started. After 8 hours of sunlight irradiation, 3 mL of the solution was taken out using a syringe. After centrifugation, the supernatant was obtained. The concentration of the remaining dye in the solution was measured at the maximum absorption wavelength (465 nm) of methyl orange. The decomposition rate was calculated according to the remaining dye concentration and the initial concentration. The results are shown in Table 1.

[0054] Examples 2 to 5, Comparative Examples 1 and 2

[0055] The glass substrate preparation methods and methyl orange dye (MO) degradation rate test methods of Examples 2 to 5, Comparative Examples 1 and 2 are basically the same as those of Example 1, except that the types of specific components and the amounts of each component are different, as shown in Table 1.

[0056] Table 1 Mass percentage of each component in the embodiments and comparative examples and methyl orange degradation rate results

[0057]

[0058] It can be seen from the table that the degradation rates of the glass substrates in Examples 1 to 5 are all greater than 50% under the test of visible light degradation of methyl orange, while in Comparative Examples 1 and 2, since no upconversion agent is contained, the degradation rates under the visible light degradation of methyl orange are much less than 50%.

[0059] In a second aspect, a chemically strengthened glass is provided. The chemically strengthened glass is obtained by chemically strengthening the above-mentioned glass substrate, and a single chemical strengthening process or a double chemical strengthening process can be used.

[0060] In a third aspect, a cover glass is provided, the cover glass comprising the glass substrate or chemically strengthened glass as described above.

[0061] In a fourth aspect, an electronic device is provided, the electronic device comprising the glass substrate, chemically strengthened glass or cover glass as described above.

[0062] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A glass substrate, characterized in that: Taking the total mass of the glass substrate as 100%, the glass substrate includes the following components in percentage by mass: SiO2: 50% to 70%; Al2O3: 4% to 20%; R2O: 12.5 to 20%; MgO: 0% to 9%; TiO2: 2% to 5%; Tb2O3+Er2O3+Ho2O3+Tm2O3: 0.05%-0.2%, wherein R2O is at least one of K2O, Na2O or Li2O.

2. The glass substrate according to claim 1, wherein The glass substrate further comprises the following components in percentage by mass: Tb2O3: 0% ~ 0.2%; Er2O3: 0.0% ~ 0.1%; Ho2O3: 0% ~ 0.2%; Tm2O3: 0% ~ 0.2%.

3. The glass substrate according to claim 1 or 2, wherein The glass substrate further comprises the following components in mass percentage: Ce2O3: 0% to 0.02%; Yb2O3: 0% to 0.5%; Define X1 = ([Yb2O3] + [Ce2O3]) / ([Tb2O3] + [Er2O3] + [Ho2O3] + [Tm2O3]), X1 is 1 to 3, wherein [Yb2O3] is the mass percentage of Yb2O3, [Ce2O3] is the mass percentage of Ce2O3, [Tb2O3] is the mass percentage of Tb2O3, [Er2O3] is the mass percentage of Er2O3, [Ho2O3] is the mass percentage of Ho2O3, and [Tm2O3] is the mass percentage of Tm2O3.

4. The glass substrate according to claim 3, wherein The glass substrate further comprises the following components in mass percentage: CaF2: 0-2%; Ge2O3: 0%-2%; CaF2+Ge2O3: 0.05%-3%.

5. The glass substrate according to claim 4, wherein X2 is 0.01 to 0.06, wherein X2 = ([CaF2] + [Ge2O3]) / [SiO2], [CaF2] is the mass percentage of CaF2, [Ge2O3] is the mass percentage of Ge2O3, and [SiO2] is the mass percentage of SiO2.

6. The glass substrate according to claim 1, wherein R2O is K2O and Na2O, and the glass substrate further comprises the following components in mass percentage: Na2O: 10% to 15%; K2O: 2.5% to 5%.

7. The glass substrate according to claim 1, wherein The glass substrate further includes the following components in percentage by mass: ZrO2: 0.2% to 0.5%.

8. A chemically strengthened glass, characterized in that: The chemically strengthened glass is obtained by chemically strengthening the glass substrate according to any one of claims 1 to 7.

9. A cover glass, characterized in that: The cover glass includes the glass substrate according to any one of claims 1 to 7 or the chemically strengthened glass according to claim 8 .

10. An electronic device, characterized in that: The electronic device includes the glass substrate according to any one of claims 1 to 7; or the chemically strengthened glass according to claim 8; or the cover glass according to claim 9.